Electrophysical and geoinformational methods of mapping the biological properties of peats - A. D. Pozdnyakova; L. A. Pozdnyakov (Бюллетень Почвенного института им. В.В. Докучаева)
It is shown that the use of electrophysical methods and GIS technologies allows revealing soil coverage structure and spatial distribution of individual biological indicators, in particular, greenhouse gases production, in drained histosols (eutrophic peat soils) located in complex landscape and hydrological conditions of the Yakhroma Valley in the Moscow Region. The combination of GIS technologies and soil electrophysics made it possible to bring together the various aspects of the soil composition and functioning. Consequently, it generates easily readable “image” of soil in a given place and at certain times. The used approach is based on the idea that the electrical resistance of soils, associated with the density of mobile charges (cations and anions of soil absorbing complex and solution), is formed under the influence of soil-forming processes and it is an integral indicator of a wide range of soil properties. Taking into account that the evolution and degradation of peatlands after their drainage is a microbiological process primarily, we paid special attention to the research in this area. The experience has been obtained in the mapping of the microbial formation of CO2, N2O and CH4 in peat soils. On the one hand, it allows estimating the current intensity of organic matter decomposition and losses of nitrogen and carbon by peat soils of different botanical composition, terms and methods of meliorations, and on the other hand, to determine the contribution of these soils to the greenhouse effect. It was established that the electrical resistance of the soil, basal, substrate-induced respiration and denitrification activity (specific form of anaerobic respiration) depend on the same set of soil properties and correlate with each other within the studied area. The high speed and productivity of electrophysical methods allow them to be used for primary soil diagnostics, selection of key points for further research, detailing the cartographic contours and refining the calculations of greenhouse gas fluxes from large areas.